Be $\lambda \in \mathbb{R}$ such that $\left | \lambda \right |> \left \| \kappa \right \|_{\infty }(b-a)$.

Prove that the solution $f^*$ of the integral equation of Fredholm $$\lambda f -\int_{a}^{b}\kappa (x,y)f(y)dy=g(x)$$ for all $x\in [a,b]$ satisfies $$\left \| f^*-\sum_{m=1}^{k}\frac{1}{\lambda ^m}\Im ^{m-1}g \right \|_{\infty }\leq \frac{\alpha ^{k}}{(1-\alpha) \left | \lambda \right |} \left \| g \right \|_{\infty }$$ for all $k\in \mathbb{N}$ where $$\alpha :=\frac{\left \| \kappa \right \|(b-a)}{\left |\lambda \right | }$$

i´m really stuck in this problem, I know that I can use that $$\Im :C_{\infty }^{0}[a,b]\rightarrow C_{\infty }^{0}[a,b]$$ is Lipschitz continuous and that linear Fredholm´s operator is linear, can anybody just give a hint please? thanks!

  • $\begingroup$ I've edited your post to hopefully fix the MathJax - it just needed dollar signs (\$) inserted around the code. Please verify that it's correct. $\endgroup$ – user61527 Oct 9 '13 at 1:42
  • $\begingroup$ after $"for all x\in[a,b] satisfies"$ in the right side of the inequality, the denominator should be $"((1-\alpha )\left | \lambda \right |)"$ $\endgroup$ – k73586 Oct 9 '13 at 1:51
  • $\begingroup$ It should be fixed now. $\endgroup$ – user61527 Oct 9 '13 at 1:52
  • $\begingroup$ This is an interesting problem. Where does it come from? $\endgroup$ – Antonio Vargas Oct 9 '13 at 2:13

Since $\lambda \ne 0$, we may write \begin{align*} f(x) - \frac{1}{\lambda}\int_{a}^{b} \kappa(x,y) f(y)\, \mathrm{d}y = \frac{g(x)}{\lambda} \end{align*} Let $\Im\colon C^{\infty}_{0} \to C^{\infty}_{0}$ be defined by \begin{align*} \Im[f](x):=\int_{a}^{b} \kappa(x,y) f(y) \, \mathrm{d}y \end{align*} Then by standard integral inequalities \begin{align*} \frac{\left|\Im[f](x) \right|}{\lambda} \le \frac{\left\|\kappa\right\|_{\infty}}{\lambda}(b-a)\left\|f\right\|_{\infty} = \alpha\left\|f\right\|_{\infty} <\left\|f\right\|_{\infty}, \end{align*} which shows that $\left\|\Im \right\|/|\lambda|\le \alpha < 1$, i.e, that $\Im/\lambda$ is a contractive linear operator on the Banach space $C_{0}^{\infty}$.

Symbolically, we can now write the equation as \begin{align*} (I-\Im/\lambda)f = g/\lambda. \end{align*} In elementary algebra, we would write $(1-x)^{-1} = \sum_{k=0}^{\infty} x^{k}$ if $|x|<1$. A similar identity holds here: \begin{align*} (I-\Im/\lambda)\sum_{m=0}^{k} \Im^{m}/\lambda^{m} &= I-(\Im/\lambda)^{k+1} \to I \text{ as } k\to \infty \end{align*} as $\left\|\Im\right\|_{\infty}/|\lambda| <1$. Hence we may write \begin{align*} (I-\Im/\lambda)^{-1} = \sum_{m=0}^{\infty} \frac{\Im^{m}}{\lambda^{m}} \end{align*} Applying this operator gives \begin{align*} f &= (1-\Im/\lambda)^{-1}g/\lambda = \sum_{m=0}^{\infty} \frac{\Im^{m}}{\lambda^{m+1}}g \\ &= \sum_{m=1}^{\infty} \frac{\Im^{m-1}}{\lambda^{m}}g \end{align*} Now the problem is easy: \begin{align*} \left\|f^{*} -\sum_{m=1}^{k} \frac{\Im^{m-1}}{\lambda^{m}}g \right\|_{\infty} &= \left\| \sum_{m=1}^{\infty} \frac{\Im^{m-1}}{\lambda^{m}}g -\sum_{m=1}^{k} \frac{\Im^{m-1}}{\lambda^{m}}g \right\|_{\infty} \\ &\le \left\|\sum_{m=k+1}^{\infty} \frac{\Im^{m-1}}{\lambda^{m-1}}\right\| \frac{\left\|g\right\|_{\infty}}{|\lambda|} \\ &\le \sum_{m=0}^{\infty} \left(\frac{\left\|\Im \right\| }{|\lambda|}\right)^{m+k} \frac{ \left\|g\right\|_{\infty} }{ |\lambda| } \\ &\le \sum_{m=0}^{\infty} \alpha^{m}\alpha^{k}\frac{\left\|g\right\|_{\infty}}{|\lambda|} \\ &= \frac{\alpha^{k}\left\|g\right\|_{\infty}}{(1-\alpha)|\lambda|} \end{align*}


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.